Intergenerational Mobility in Latin America - Jere R. Behrman; Alejandro Gaviria; Miguel Székely (Inter-American Development Bank, Research Department, 2001)
High inequality has long been regarded as one of the main problems facing Latin American countries. To understand better the determinants of inequality and to help guide thinking about policy options, it is useful to know whether inequality mainly reflects low intergenerational mobility or whether it is driven by differences in individual characteristics that arise independently of family background. In this paper we use five household surveys with questions about parental socioeconomic characteristics for adults, and a set of 112 standard household surveys to examine the intergenerational transmission of schooling and occupational status in Latin America and the United States. We find that intergenerational mobility is much higher in the United States than in Latin America, that there are sizable differences in mobility within Latin America, and that mobility in Latin America is strongly associated with schooling levels and expenditures on education.
Keywords: 330; Soziale Mobilität; Generationengerechtigkeit; Einkommensverteilung; Lateinamerika